Rhynchonema dighaensis sp. nov. (Monhysterida: Xyalidae): a marine nematode from the Indian coast with an illustrated guide and modified key for species of Rhynchonema Cobb, 1920 - Datta, Tridip Kumar; Navarrete, Alberto De Jesus; Mohapatra, Anil (Zootaxa, 2015)
A small bodied, free-living marine nematode, Rhynchonema dighaensis sp. nov., is described from the intertidal sand of the east coast of India. It is characterized by having a small buccal cavity, longer left spicule and symmetrical dorsal gubernaculum apophysis. Other species of the genus are discussed with their type locality. A modified key has been prepared for species of Rhynchonema with an illustrated guide. Species of Rhynchonema primarily differ from each other by the shape and size of the spicules, shape of the gubernaculum and dorsal apophysis, size of the buccal cavity and position of the amphid.